The Meaningful Use of Electronic Health Records and Health Care Quality. (November 2015) - Kern, Lisa M.; Edwards, Alison; Kaushal, Rainu; ,
The federal government is investing approximately 30 billion in incentives for adoption and meaningful use (MU) of electronic health records (EHRs). Whether achieving MU improves quality of care is unclear. The researchers conducted a longitudinal study of 514 primary care physicians in New York State from 2010 to 2011. Quality of care provided by those who achieved stage 1 MU was compared with the quality provided by those who used EHRs but did not achieve stage 1 MU. Generalized estimating equations were used to determine whether receipt of MU incentives was independently associated with performance on 9 MU quality measures. In 2011, 44% of physicians achieved MU and 56% did not. No difference in quality was found between those who achieved stage 1 MU and those who were using EHRs but had not achieved MU. Longer follow-up is needed to observe the full effects of this multistage national policy.